ANALISIS KESULITAN PENGUASAAN KOSAKATA BAHASA ARAB PADA SISWA (Universitas Negeri Semarang, 2023)
So far mufrodat (vocabulary) has had a great influence and the number is not limited to learning Arabic. There are many ways for a beginner to master Arabic mufrodat (vocabulary). However, in reality, students often face various learning difficulties in the process of mastering mufrodat (vocabulary). This study aims to describe the factors that cause difficulties faced by students in mastering Arabic mufrodat (vocabulary) at MTs Muhammadiyah 03 Nogosari and to describe steps to overcome difficulties in mastering Arabic mufrodat (vocabulary) at MTs Muhammadiyah 03 Nogosari. This research is a type of field research with a qualitative approach. The data is in the form of learning difficulties in mastering mufrodat and steps to overcome difficulties with student and teacher data sources. Research data analysis using data collection techniques in the form of observation, interviews and documentation. The results of the research, the researchers found the factors that cause students' learning difficulties in mastering Arabic mufrodat (vocabulary) according to the classification made by the researcher, namely internal factors and external factors. Internal factors include the lack of student interest and low reading ability. While external factors include misuse of mobile phones and the methods given by the teacher.